Pecegahan Radikalisme Melalui Pembiasaan Tradisi Islam Nusantara di MI Najmul Huda Kemloko Temanggung - Idammatussilmi Idammatussilmi (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2018)
This study aims to describe the context of deradicalism through the habituation of the Nusantara Islamic tradition. The development of radicalization led to widespread of social unrest. Through the habituation of the Nusantara Islamic tradition was believed as being able to prevent the proliferation of radicalization. This serearchis a descriptive study using a qualitative approach with triangulation (combined) data collegtion techniques. The serearch was coductedon the students of MI Najmul Huda Kemloko that produce finding that by habituating the Nusantara Islamic tradition can increase awareness of the importance of harminy in diversity. In accordance with the command of Islam to do good to all creatures of Allah by doing fair, tolerance, love, and loving for each other among fellow creature. The habituation of Nusantara Islamic tradition of the archipelago by holding mujahadah and pilgrimage to the grave at MI Najmul Huda Kemloko by hoping that students can understand that Islam actually teaches peace. By carring out the Nusantara Islamic tradition that must be preserved, student must understand the basisi of mujahadah and the pilgrimage of the grave so that there is no misappropriation. The Habituation of the Nusantara Islamic tradition has great potential to counteract the growing flow of radical Islamic group